Andahuaylas, 1974: A peasant demand movement within the agrarian reform process - Palomino, Abdón (1978)
In the second half of 1974, when the agrarian reform in compliance with DL 17716 was in rapid application and when the reformism of the province of Andahuylas, department of Apurímac, organized in the Provincial Federation of Peasants of Andahuylas (FEPCA), frustrated in Waiting in vain for the advent of agrarian reform, they took the initiative to invade the haciendas and expel the landowners. There are several political events in the context of which the Andahuaylas peasant mobilization takes place: the expropriation of newspapers with national circulation, which sharpens the already tense relationship between the Military Government and sectors of the Peruvian right, the activation of popular movements and the Assembly of the National Agrarian Confederation (CNA), as an instance of mediation between the peasants who are beneficiaries of the agrarian reform and the Government.